Psychological and behavioral characterization of suicide ideators and suicide attempters in adolescence - Coci, Chiara; Invernizzi, Roberta; Capone, Luca; Casini, Erica; Orlandi, Marika; Galli, Paola; Rossi, Ilaria; Martinelli, Ottaviano; Borgatti, Renato; Mensi, Martina Maria; , the Northern Italian Suicidality Research Group (Frontiers in Psychiatry, 2022)
Suicide is a global cause of death, a chronic disability, and a significant public health problem. Recent works emphasize the importance of differentiating people with suicide ideation (SI) and people with suicidal attempts (SA), so we conducted a clinical cross-sectional study to better characterize the features most associated with SA. We enrolled 88 adolescents (77 females) from 12 to 18 years of age (M = 15.21, SD = 1.63) admitted to Northern Italian Child Neurology and Psychiatry Service who presented SI and/or SA. We conducted an assessment using the Columbia-Suicide Severity Rating Scale, and divided participants into two groups: adolescents with SA, and adolescents with thoughts about killing themselves which may include a plan but no suicidal attempts (SI). We found that the SA group showed greater severity of SI [t(86) = −3.485, p < 0.001], higher levels of subjective depression [t(70) = −2.65, p = 0.01)], and a higher prevalence of personality disorders [χ(3)2 = 8.775, p = 0.032] than the SI group. Both groups presented a prevalence of internalizing problems compared to the externalizing ones in the Youth Self-Report (YSR). Higher scores on YSR internalizing problems correlate positively with the “Repulsion by Life” subscale of the Multi-Attitude Suicide Tendency (MAST) Scale in both SA and SI groups (p = 0.41 and p = 0.67, respectively), while low levels of the MAST “Attraction to Life” subscale appear more often in the SA one (p = −0.71). In conclusion, results showed that some features (e.g., prevalence of personality disorders, SI intensity, and subjective depression) might help clinicians distinguish between patients with SI and those with SA and support the importance of carefully pursuing this distinction in research.